ANALYSIS OF CASH TURNOVER AND INVENTORY TURNOVER ON ECONOMIC RENTABILITY: THE ROLE OF LIQUIDITY AS A MODERATING VARIABLE - Jamil, Alief Rasika; Yuliati, Yuliati (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2025)
In the era of increasingly advanced globalization, corporations are encouraged to innovate and improve efficiency, one of which is consumer cyclicals companies. This study focuses on analyzing the influence of cash turnover and inventory turnover on economic profitability with liquidity as a moderation variable. Using a quantitative approach and secondary data from financial statements recorded on the Indonesia stock exchange for the 2021-2023 period, the purposive sampling method used for the selection of the sample of this study involving 30 companies and the data was analyzed using Eviews 12. The results of the study show that cash flow has no effect on economic efficiency. Inventory turnover has a positive effect on economic profitability. Liquidity has been proven to moderate the effect of cash turnover on economic profitability, but it does not moderate the influence of inventory turnover on economic profitability. This research provides important insights for the Company's management in improving the efficiency of cash and inventory management, as well as providing a reference for investors in evaluating the company's financial performance in this sector.